'A lot of gay energy in the city': An identity-based exploration of leisure travel to domestic cities for rural queer people in Australia. (March 2023) - Lewis, Clifford; Mehmet, Michael; McLaren, Suzanne
Abstract: Using identity-based motivation theory, this study explored the perceived role leisure travel to domestic cities played for rural queer people in Australia. Eleven semi-structured interviews were conducted and revealed that travelling to the City helped queer people construct their social identity by providing opportunities that may be restricted or limited at home. Further, those who were still defining their self-identity and/or lived in rural areas that were less tolerant of queer people, used travel to escape the rigours of self-regulation, uncompromising heterosexuality, intolerance, and hostility. Participants felt safer and more comfortable in cities as anonymity, a strong visible representation of the queer communities, and acceptance of queer people allowed them to be themselves and explore the depths of their identity. The results suggest there is an opportunity for queer spaces and experience providers in the City to target rural queer people based on their identity needs.